Economies of Vertical Integration in the Japanese Water Supply Industry - Takuya Urakami (European Regional Science Association (ERSA), 2006)
The merging of some water utilities in Japan has become possible since the 2000 Outline of Administrative Reform and the 2001 Water Act Revision. There are two avenues to merge water utilities, horizontal consolidation and vertical integration. Horizontal consolidation enables water distributors, such as the large water supply systems, to merge into one. Vertical integration enables water distributors and water wholesalers, such as the bulk water supply systems, to merge into one. However, these wide area consolidations or integrations havenft been promoted at local government level due to an absence of authority. Further, promotion has also been hindered by the lack of previous studies to support the economies of wide area consolidations or integrations. This paper focuses especially on the vertical integration between the water intake-purification and water distribution stages. To investigate economies of vertical integration, I estimate translog cost function in the Japanese water supply industry and test the separability hypotheses among water intake, purification and distribution stages. The results show that the economies of vertical integration exist between the water intake-purification and water distribution stages, so that the bulk water supply systems and the large water supply systems will be able to merge in order to achieve greater cost efficiency.
Keywords: 330